Functional Characterization Of Styr-3 Non-Protein-Coding Rna (npcRNA) In Salmonella enterica serovar Typhi - Kumar, Thiviyaa M. Othaya (2014)
Non-protein-coding RNAs (npcRNAs) are RNA molecules that do not encode for proteins but are involved in modulating a myriad of cell regulatory processes, including bacterial drug resistance mechanisms. In this study, a novel npcRNA, StyR-3; discovered from the genome of S. Typhi was selected for further characterization via bioinformatics and experimental-based approaches. This 144-nt intergenic npcRNA is located in the ramRA regulon of S. Typhi Ty2. The bioinformatics-based characterization showed that it is highly conserved among Salmonella species; besides having a stable secondary structure as was predicted by LocaRNA software.